The Abolition of Culpability After Converting to Islam In The Science of Ḥadîth and Ḥadîth Al-Aḥkâm Perspective - Athoillah, Mohamad Anton; Nuryamin, Nuryamin (al-'adalah, 2020)
This article examines the authenticity of the hadith concerning the abolition of one's culpability after converting to Islam as contained in Ṣaḥîḥ al-Bukhârî, Kitab al-Îmân, Bâb Ḥusn Islâm al-Mar '. The method used in this research is the takhrîj al-ḥadîth method, which is a method to find the strength of the authenticity of ḥadîth by tracing it to its original source. This research found the fact that in the narrative, many ḥadîth in the book Ṣaḥîḥ al-Bukhârî are often classified as Hadith al-mu'allaq (Suspended Hadith) without considering the statements or explanations of the commentators. In fact, the status of a ḥadîth which is categorized as ḍa'îf (weak) because the sanad (chain of narrators) is munqaṭi ' (broken), but after tracking other sanad there is an indication that the ḥadîth is connected to the Prophet, so that the status is ṣaḥîḥ (authentic). This has been the agreement of the scholars, except for Ibn Ḥazm. In conclusion, not all ḥadîths, categorized as Mu'alla, can be categorized as ḍa'îf (weak) because the sanad is munqaṭi '(the narrator's chain is broken); As, in many cases, there are many such ḥadîths, after tracking through other means, it turns out to be connected to the Prophet; One of which is the hadith regarding the elimination of past mistakes of an infidel who later converted to Islam.